Recommendations for the integration of enhanced publications in trustworthy digital repositories - Arraiza, Paloma Marin [UNESP]; Ventura Amorim Goncalez, Paula Regina; Borsetti Gregorio Vidotti, Silvana Aparecida [UNESP] (Univ Federal Santa Catarina, 2019)
Objective: Establish recommendations for the integration of enhanced publications into trustworthy digital repositories. Enhanced publications are configured as composite digital objects and are acquiring relevance in scientific research as a way of sharing research data. Methods: This paper uses exploratory qualitative research that analyses enhanced publications and the approaches present in the literature, as well as current initiatives for archiving research objects in repositories. In addition to the analysis, the general requirements for trustworthy digital repositories of the Research Library Group (RLG) and Online Computer Library Centre (OCLC), the guidelines of ISO 16363:2012 and the requirements for information systems that work with extended publications are combined. Results: We propose a series of recommendations and execution methods for the integration of enhanced publications into trustworthy digital repositories. Conclusions: These recommendations can serve as a basis for future repository developers who want to build a solid framework for such publications.
Keywords: Enhanced publications; Multimodal scholarship; Trustworthy digital repositories; Information infrastructure